2022
DOI: 10.3390/nano12101768
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Modified Porous Perovskite-Type LaFeO3 for Efficient Ethanol Detection

Abstract: Perovskite (ABO3) nanosheets with a high carrier mobility have been regarded as the best candidates for gas-sensitive materials arising from their exceptional crystal structure and physical–chemical properties that often exhibit good gas reactivity and stability. Herein, Ag in situ modified porous LaFeO3 nanosheets were synthesized by the simple and efficient graphene oxide (GO)-assisted co-precipitation method which was used for sensitive and selective ethanol detection. The Ag modification ratio was studied,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Zhang et al [ 26 ] reported the response of 221.99 to 100 ppm ethanol using porous Co 3 O 4 with a specific surface area of 28.509 m 2 /g. For perovskite-type oxides, LaFeO 3 has been tested by some research groups [ 27 , 28 ]. Dai et al [ 27 ] prepared LaFeO 3 thin film with the periodic pores of 500 nm in dimension and yielded the response of 14 to 5 ppm ethanol at 450 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 26 ] reported the response of 221.99 to 100 ppm ethanol using porous Co 3 O 4 with a specific surface area of 28.509 m 2 /g. For perovskite-type oxides, LaFeO 3 has been tested by some research groups [ 27 , 28 ]. Dai et al [ 27 ] prepared LaFeO 3 thin film with the periodic pores of 500 nm in dimension and yielded the response of 14 to 5 ppm ethanol at 450 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Dai et al [ 27 ] prepared LaFeO 3 thin film with the periodic pores of 500 nm in dimension and yielded the response of 14 to 5 ppm ethanol at 450 °C. Yu et al [ 28 ] prepared the Ag-modified LaFeO 3 with a specific surface area of 16.45 m 2 /g and obtained the response value of 20.9 to 20 ppm ethanol at 180 °C. It is thus obvious that high specific surface area or small particle size of p-type semiconducting oxides is a critical factor for a highly sensitive VOC detection.…”
Section: Resultsmentioning
confidence: 99%
“…The carriers of the n-type semiconductor increase, so the resistance becomes larger; the carriers of the p-type semiconductor decrease, so the resistance becomes smaller [30][31][32]. In addition to single metal oxides, bimetallic metal oxides have also been used as gas sensing materials in recent years [33], including NiCo 2 O 4 [34], ZnCo 2 O 4 [35], and LaFeO 3 [36]. Even though MOS possess the above advantages, high operating temperature and low selectivity are still their bottlenecks as gas sensors [37].…”
Section: Introductionmentioning
confidence: 99%
“…Also, since the work function of the substrate is lower than that of the noble metal, when they are in contact with each other, free electrons on the surface of the substrate are transferred to the noble metal, which deepens the thickness of the electron depletion layer and creates an additional Schottky potential at the interface base . Yu et al deposited Ag on LaFeO 3 nanosheets by the coprecipitation method and exhibited a high response to ethanol, completing the whole adsorption–desorption process in 53 s.…”
Section: Introductionmentioning
confidence: 99%
“…Also, since the work function of the substrate is lower than that of the noble metal, when they are in contact with each other, free electrons on the surface of the substrate are transferred to the noble metal, which deepens the thickness of the electron depletion layer and creates an additional Schottky potential at the interface base. 17 Yu et al 18 deposited Ag on LaFeO 3 nanosheets by the coprecipitation method and exhibited a high response to ethanol, completing the whole adsorption−desorption process in 53 s. Perovskite-type LaFeO 3 , as a wide-band oxide semiconductor, is well known because of its unique nanostructure and mixed conductive mode and is widely used in catalysts, 19,20 fuel cells, 21 solar cells, 22 and gas sensors. 23 However, the performance of LaFeO 3 alone is not outstanding, and some modifications are usually needed to improve its performance.…”
Section: Introductionmentioning
confidence: 99%